Description of clean chip residual forest harvest and its availability for horticultural uses in the southeastern United States - Boyer, Cheryl R.; Gallagher, Thomas V.; Gilliam, Charles H.; Fain, Glenn B.; Torbert, H. Allen; Sibley, Jeff L. (My University, 2013)
Residual chipping material, also called clean chip residual (CCR), has potential use as a growth substrate in the nursery and greenhouse horticultural industries. A survey was conducted in the southeastern United States among companies conducting harvesting operations on pine (Pinus sp.) plantations for the production of pulpwood in the forest industry. Fourteen operators in four states (Alabama, Mississippi, Georgia, Florida) were visited to evaluate the on-site status of residual material. Sample analysis of CCR revealed that it was composed of ≈37.7% wood (range, 14.2% to 50.5%), 36.6% bark (range, 16.1% to 68.5%), 8.8% needles (range, 0.1% to 19.2%), and 16.9% indistinguishable (fine) particles (range, 7.5% to 31%). pH ranged from 4.3 to 5.5 for all locations and electrical conductivity (EC) averaged 0.24 mmho/cm. Most nutrients were in acceptable ranges for plant growth with the exception of three sites above recommended levels for iron and four sites for manganese. Survey participants estimated that ≈27.5% of the harvest site biomass was composed of CCR. Some harvesters were able to sell CCR as fuelwood to pulp mills, while others did not recover the residual material and left it on the forest floor (44.3% total site biomass). Operations in this survey included typical pine plantation chipping and grinding operations (harvesters), woodyards (lumber, fuelwood, etc.), and operations processing mixed material (salvage from trees damaged in hurricanes or mixed tree species cleared from a site that was not under management as a plantation). Residual material varied depending on the plantation age, species composition, site quality, and natural actions such as fire. Average tree age was 11.5 years (range, 8 to 15 years), while average tree stand height was 37.0 ft (range, 25 to 50 ft) and average diameter at breast height (DBH) was 5.9 inches (range, 4 to 7 inches). Residual material on site was either sold immediately (28.6%), left on site for 1 to 3 months (28.6%), left on site for up to 2 years (7.1%), or not collected/sold (35.7%). Several loggers were interested in making CCR available to horticultural industries. Adequate resources are available to horticultural industries, rendering the use of CCR in ornamental plant production a viable option.
Keywords: CCR; Substrate; Alternative media; Wood fiber; Bark; Forestry; Greenhouse; Nursery